CHANGES IN ENDOTHELIAL NO-SYNTHASE IN PREGNANT WOMEN WITH CHRONIC ARTERIAL HYPERTENSION AND SMOKING - Бичан, Николай Андреевич; Рублевская, Алина Сергеевна; Мальцева, Нина Васильевна; Осокина, Валентина Родионовна; Черных, Наталья Степановна (Medicine in Kuzbass, 2021)
Methods. The changes in endothelial NO-synthase (eNOS) were studied as a manifestation of endothelial dysfunction in 670 pregnant women, depending on arterial hypertension (AH) and smoking. Chronic hypertension had 313 pregnant women, 20 % of women included in the study smoked. All women are divided into 4 groups. Group 1 (control) included 313 healthy non-smoking pregnant women without AH, the second group included 250 non-smoking pregnant women with AH, the group 3 included 45 smoking pregnant women without AH, group 4 included 62 smoking pregnant women with AH. The groups did not differ in average age and gestational age. Endothelial NO-synthase was measured in blood serum by using a RayBiotech reagent (RayBio Human eNOS ELISA Kit) by a plate method.Results. It was found that in the group 2 the level of eNOS was 30.7 % lower than in the control group, but this difference was no statistically significant (2.6 ng/ml versus 1.8 ng/ml, p = 0.014). In the group 3 the level of eNOS was statistically significantly lower than in the control group: 1.3 (0.3-2.5) ng/ml versus 2.6 (1.6-9.4) ng/ml (p = 0.01). In the group 3 level of eNOS was 27.8 % lower than in the group 2, however, this difference were no statistically significant: 1.3 (0.3-2.5) versus 1.8 (1.0-3.4), p = 0.19. The lowest level of NO-synthase was registered in the group 4 (AH + smoking) – 0.6 (0.1-1.0) ng/ml. It is statistically significantly lower than in the control group (p < 0.001), in the group 2 – 1.8 (1.0-3.4) ng/ml (p = 0.001) and in the group 3, respectively – 1.3 (0.3-2.5) ng/ml (p = 0.02).Conclusions. Smoking and especially smoking in combination with arterial hypertension caused a significant decrease in endothelial NO-synthase in pregnant women, which indicates the development of endothelial dysfunction.
Keywords: pregnancy; arterial hypertension; smoking; endothelial NO synthase (eNOS); endothelial dysfunction